HUBUNGAN KENAKALAN REMAJA DAN FUNGSI SOSIAL KELUARGA DENGAN PRESTASI BELAJAR SISWA KELAS XI TATA BOGA SEKOLAH MENENGAH KEJURUAN NEGERI 4 YOGYAKARTA - Oktavia Ersalina Gultom; Endang Wani Karyaningsih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The purpose of this study was to find out, 1) a negative relationship between juvenile delinquency and learning achievement, 2) a relationship between the social function of family and the learning achievement, and 3)  a relationship between juvenile delinquency and social function of family on learning achievement  in class XI student  Majoring in Vocational Culinary 4 Yogyakarta.  This research includes the study of ex post fact. Methods of data collection using questionnaires and documentation testing instrument research. Technique of analysis data using descriptive analysis and hypothesis testing  using multiple regression test was preceded two predictor test requirements analysis is the normality test, linearity and zero level. The result showed that 1) there is no negative relationship between juvenile delinquency and learning achievement with relationship coefficient  of -0,098<0,18, 2)There is a positive relationship and the significant social function of family and learning achievement with relationship coefficient of 0,350>0,181. 3) there is a significant positive relationship juvenile delinquency and family social functions together with learning achievement with relationship coefficient of 0,649>0.181. and F count =11,693<F table =3,09. Determinant coefficient  between juvenile delinquency family social functioning and academic achievement of 0,220 means that juvenile delinquency and social function the family to contribute to learning achievement of 22 % delinquency relative contribution amounted to 39,94% on learning achievement  and function family social relative contribution of 60,06) on learning achievement. Juvenile delinquency give effective contribution of 8,78% on the learning achievement and social function of family give the effective contribution amount to 13,22% of the learning achievement with a total of 22%.